Penilaian Pemberian Kredit Untuk Meminimalisir Resiko Kredit Pada Bank BRI Unit Tampan Kota Pekanbaru - Misral Misral; Randi Finowa (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2021)
This study aims to determine the effect of applying the 5C principle in the assessment of credit disbursement to minimize credit risk at the handsome Unit BRI Bank Pekanbaru City. Data collection was carried out by distributing questionnaires to the handsome unit BRI financing department as many as 8 respondents. This research uses descriptive quantitative method with Accidental Sampling sampling technique. The data obtained were then processed using the tools of IBM SPSS Statistics 26. The results of this study show that the Handsome Unit of the BRI Bank applies the 5C principle well in the assessment of credit granting efforts to minimize credit risk.